AN APPRAISAL OF THE LEGAL CAPACITY AND CONTRACTUAL RIGHT OF THE CHILD UNDER THE CHILD’S RIGHT ACT, 2003. - Abubakar Mohammed Bokani, Ph.D (ABUAD Law Journal, 2024)
It is a fundamental principle of law of contract that parties to contract are at liberty to enter into contract, and agree on the terms of the contract. Accordingly, the Child’s Right Act, 2003 (CRA 2003) and other Child’s Right laws of various states in Nigeria confer the child with the right to enter into contract. However, the law seems to limit the contractual right and capacity of the child to contract of necessaries. Consequently, a child does not possess the requisite legal capacity and right to enter into contracts in respect of non-necessaries. Unfortunately, CRA 2003,s 18 does not define what constitutes ‘necessaries’ and the effect of such void contracts. This article deployed doctrinal research method to appraise the legal capacity and contractual right of the Child in Nigeria, and the objective is to determine the scope of the contractual right and capacity of the Child and legal effect of contracts of non-necessaries.Thus, the question is, what is the extent of the contractual right of the child in Nigeria? This article found that the lack of definition of what constitutes necessaries in CRA 2003 has created uncertainty in the scope of the contractual right and capacity of the child in Nigeria. More so, CRA 2003 s18 is oblivious to the principle of ‘best interest of the child’ which is the philosophy that underpins contracts involving the child. It was thus recommended that the CRA 2003, s18 and similar laws should be amended to adopt the common law definition of what constitutes ‘necessaries’. In addition, contract of non-necessaries entered into by the child should not be treated as void ab initio. Rather, they should be construed as voidable against the child but binding on the adult.